2011
DOI: 10.1016/j.seizure.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An atypical case of Lennox-Gastaut syndrome not associated with mental retardation: A nosological issue

Abstract: The characteristic electroclinical features of Lennox-Gastaut syndrome (LGS) have been extensively reported, but the influence of the constellation of slow spike-and-wave (SSW) complexes with multiple seizure types (including atypical absence seizures [AAS] and tonic seizures [TS]) on patients with this syndrome is still unclear. We report the case of a 28-year-old woman who developed AAS and brief asymmetric TS at the age of 14 years. Her seizure disorder met diagnostic criteria for LGS (SSW on electroencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Lennox-Gastaut syndrome (LGS) is one of the most severe epileptic encephalopathies with childhood onset. It is characterized by the presence of (i) multiple, untreatable seizure types, including tonic seizures, atypical absences and tonic or atonic drop attacks, and (ii) electroencephalographic (EEG) abnormalities, consisting of interictal pattern of slow-spike waves (SSW) < 3 Hz, and paroxysmal fast rhythms (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), mainly during non-REM sleep [1]. At the onset of the disorder, not all the different seizure types can be present [2].…”
Section: Definition Epidemiology and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Lennox-Gastaut syndrome (LGS) is one of the most severe epileptic encephalopathies with childhood onset. It is characterized by the presence of (i) multiple, untreatable seizure types, including tonic seizures, atypical absences and tonic or atonic drop attacks, and (ii) electroencephalographic (EEG) abnormalities, consisting of interictal pattern of slow-spike waves (SSW) < 3 Hz, and paroxysmal fast rhythms (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), mainly during non-REM sleep [1]. At the onset of the disorder, not all the different seizure types can be present [2].…”
Section: Definition Epidemiology and Etiologymentioning
confidence: 99%
“…In cryptogenic cases, the psychomotor development of the child is generally normal before the onset of the disease and then deteriorates. However, the early onset, the presence of tonic seizures, certain EEG patterns and the overuse of antiepileptic drugs (AEDs) are risk factors for ID; on the contrary, the late onset, the presence of subclinical seizures without falls would have a positive role on cognitive functions [11].…”
Section: Cognitive Impairment and Behavioural Disturbancesmentioning
confidence: 99%
“…Cognitive impairment in LGS appears related to the age of onset and persistence of seizures. An earlier age of seizure onset (<5 years) has been associated with more severe cognitive impairment, while patients who develop LGS later in life (>9 years) follow a more favorable cognitive course ( 3 , 30 , 32 , 41 43 ). In a group of patients with normal mental development before the onset of LGS, Ohtsuka ( 44 ) found that 95.7% (22/23) of patients with persistent seizures showed cognitive impairment after a follow-up period of at least 5 years compared with 12.5% (1/8) of patients who had been seizure free for at least 1 year.…”
Section: Lennox–gastaut Syndrome – Definition and Clinical Featuresmentioning
confidence: 99%
“…2,3,17 Up to 10 to 20% of patients with LGS reaches acceptable ranges of intellectual functioning despite variable limitations in daily activities and cases of lacking cognitive impairment have been recently reported. 2,28 Main risk factors for intellectual delay in LGS include earlier age of onset, a previous West syndrome, a symptomatic etiology, and episodes of nonconvulsive status epilepticus. 1,2,17,29…”
Section: Clinical Presentationmentioning
confidence: 99%